A study of disparities in the socio-economic development of eastern Uttar Pradesh, India - Anil Kumar Tiwari,; Ravindra K. Pandey,; Vishwambhar Nath Sharma, (National Geographical Journal of India, 2021)
The socio-economic development of a region depicts overall improvement in poverty conditions and resource availability. It is a continuous process to meet the social and economic necessities of the people. Eastern Uttar Pradesh, an economically backward region due to lack of infrastructure and high concentration of population, shows the high disparity in socio-economic development. This work is an attempt to estimate the levels of socio-economic development of this region. Indicators used to measure the level of socio-economic development of the study area are per capita energy consumption, percentage of workers to total population, per capita income, literacy rate, number of health care centers per lakh population and number of schools per lakh population. Results show that Varanasi, Ambedkar Nagar, Sultanpur, Ghajipur, Jaunpur, Sant Kabir, Sant Ravidas Nagar, Pratapgarh, Deoria, Mau and Faizabad are highly developed while Districts of Vindhyan and Terai area are poorly developed due to poor infrastructure and awareness.